Answer:
Step-by-step explanation:
x² + 4x - 1 - x =x² + 4x -x - 1 { bring the like terms together and add}
= x² + 3x - 1
I would honestly say either b or d but I'm not completely sure most likely b
It would either be that they Miss-counted the hot dog buns that they put into each pack or that they put 7 buns on purpose
Answer: its -0
Step-by-step explanation:
PEMDAS.
Parentheses
Exponents
Multiplication
Division
Addition
Subtraction
Lets apply that here.
72-[(3x2^3)+48]
So first we start with (3x2^3)
2^3=8
3*8=24
now we do 24+48 which equals 72
now we have 72-72 which equals zero.
So
72-[(3x2^3)+48] = 0